Evaluating visitor usage and safety perception experiences in National Forest Parks - Zhao, Jing; Abdul Aziz, Faziawati; Song, Menglin; Zhang, Hui; Ujang, Norsidah; Xiao, Yi; Cheng, Ziyi (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Various physical and environmental factors affect the recreational experience in national forest parks. Understanding visitors’ preferences regarding these factors is significant for promoting the physical and mental health and well-being of urban residents. This study aims to quantify residents’ usage patterns and safety perceptions of national forest parks. It focuses particularly on Santai Mountain National Forest Park in Jiangsu, China, and conducted a semi-structured questionnaire survey with 688 participants. The statistical software IBM SPSS Statistics 24 was used for data analysis. A descriptive quantitative analysis was conducted on the respondents’ demographic information. Descriptive statistics, chi-square tests, and an ordinal logistic regression model were employed to analyze the survey data. The survey results show that most visitors go to the forest park only once or twice a year, usually on weekends, holidays, and during leisure time rather than on workdays. Because the national forest park is located in the suburbs, the journey is long, and most visitors choose to drive there. Additionally, the majority of visitors go to the forest park with family and friends. Because the park is well managed and has complete safety facilities, most visitors feel safe in the national forest park. © 2024 by the authors.